2015
DOI: 10.1021/acs.biochem.5b00547
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Liprotides To Stabilize and Transport Hydrophobic Molecules

Abstract: Recently, it has been shown that different complexes consisting of protein and fatty acids, which we call liprotides, have common functional and structural features. Liprotides can transfer their fatty acid content to membranes, highlighting the potential to incorporate other small molecules and help transfer them to membranes. In this study, this potential was explored with regard to the poorly water-soluble vitamin E compound α-tocopherol (Toc). Uptake into liprotides increased Toc solubility and chemical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Since much of the OA in solution should be bound in the complex at these concentrations, folding is most likely limited by having a too small tOmpA:OA ratio rather than by having too much free OA in solution. Data from SAXS suggest that each liprotide contains around 30 OA molecules, in good agreement with earlier findings . Since around 40 OA molecules per tOmpA is needed to achieve a 50% folding it is likely that folding of tOmpA required more than one liprotide or that one liprotide can provide extra OA to another liprotide to assist in OmpA folding.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Since much of the OA in solution should be bound in the complex at these concentrations, folding is most likely limited by having a too small tOmpA:OA ratio rather than by having too much free OA in solution. Data from SAXS suggest that each liprotide contains around 30 OA molecules, in good agreement with earlier findings . Since around 40 OA molecules per tOmpA is needed to achieve a 50% folding it is likely that folding of tOmpA required more than one liprotide or that one liprotide can provide extra OA to another liprotide to assist in OmpA folding.…”
Section: Discussionsupporting
confidence: 89%
“…In the liprotides, OA is covered by a protein shell which mediates OA's contact with its surroundings. Earlier studies have shown that the liprotides can easily interact with membranes and transfer its OA content . To test the effect of the liprotide protein shell on tOmpA folding kinetics, we compared folding rates of tOmpA in liprotide, DDM and small unilamellar vesicles (SUV) of DLPC (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional binding occurs at higher [OA], however, and at the third point (halfway between point 2 and the baseline, set to 0 kcal mol −1 ) we see binding of 21.6±1.8 OA/aLA. Remarkably, this ratio corresponds to that seen with liprotides when large amounts of OA are mixed with aLA and separated by gel filtration (21±5 OA/aLA) . At all three transitions, the amount of unbound OA was essentially zero within error ( y ‐axis intercept in Figure B and Table S2), thus confirming that all of the OA complexes with aLA.…”
Section: Resultsmentioning
confidence: 99%
“…In a complementary version of the protein:fluorinated surfactant complexes, liprotides transfer fatty acids to membranes while proteins are released 49 , which is probably the basis for their biological activity. This transfer ability highlights their possible use as host-guest systems for the transport of hydrophobic and sensitive molecules such as vitamins 50 which can be solubilized in the micellar interior. The elucidation of liprotide structures provides a remarkable link between the physical-chemical world of protein-surfactant complexes and biologically potent agents.…”
Section: Shaping Up: Modelling Protein-surfactant Complexes and Protementioning
confidence: 97%